Ultra-relativistic effects of laser beam and electron interactions : basic equations, exact solutions and modelling - Popa, Alexandru (Alexandru Mircea) (IOP (Series). Release 21., 2021)
The latest generation of high-power pulsed lasers has renewed interest in the ultra-relativistic effects produced by the interaction between laser beams and electrons. Synthesising previous research, this book presents a unitary treatment of the main effects that occur in the ultra-relativistic interactions between laser beams and electrons. It uses exact solutions of relativistic and classical quantum equations, including a new solution of the Dirac equation, to fully describe the field and model the main ultra-relativistic effects created within it.